2011
DOI: 10.1007/dcr.0b013e318217586f
|View full text |Cite
|
Sign up to set email alerts
|

Patient Characteristics and Treatment Outcome in Functional Anorectal Pain

Abstract: Biofeedback is beneficial in the subset of patients with functional anorectal pain and difficulty with defecation. Tricyclic antidepressants, Botox, and sacral nerve stimulation may also have a role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 20 publications
2
29
0
8
Order By: Relevance
“…Long-term pain can inevitably cause psychological disturbance. Depression is more severe in patients with FARP as some researchers reported that depression occurs in about 30% of FARP patients [25, 26]. Since depression and anxiety were assessed at the time of pain diagnosis, we were unable to draw a conclusion whether pain precedes psychological disturbance.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Long-term pain can inevitably cause psychological disturbance. Depression is more severe in patients with FARP as some researchers reported that depression occurs in about 30% of FARP patients [25, 26]. Since depression and anxiety were assessed at the time of pain diagnosis, we were unable to draw a conclusion whether pain precedes psychological disturbance.…”
Section: Discussionmentioning
confidence: 96%
“…Still, a large percentage of patients do not respond to any pain treatment. In a study with 80 cases of FARP patients, Gary K [26] found that only 46.3% of patients had reduced pain after treatment, while the majority did not respond to the treatment. Perhaps combination therapies will reach higher treatment efficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…7 In another noncontrolled study of 158 patients with chronic anorectal pain, symptoms improved after biofeedback therapy (17/29 patients [58.6%]), tricyclic antidepressants (10/26 patients [38.5%]), botulinum toxin injection (5/9 patients [55.5%]), and sacral nerve stimulation (2/3 patients [66.6%]). 33 …”
Section: Methodsmentioning
confidence: 99%
“…Physical activity may be another option, but studies examining the effect of physical therapy on constipation in PD are lacking. Biofeedback was tested to be effective in patients suffering from anorectal dysfunction [52] and constipation [53] and it might be an interesting therapeutical option in PD patients.…”
Section: Non-pharmacological Treatment Optionsmentioning
confidence: 99%